2020
DOI: 10.1002/lt.25771
|View full text |Cite
|
Sign up to set email alerts
|

Bile Composition as a Diagnostic and Prognostic Tool in Liver Transplantation

Abstract: Bile secretion and composition reflects the functional status of hepatocytes and cholangiocytes. Bile composition can have a role in the assessment of donor grafts before implantation in the recipient. In addition, changes in bile composition after liver transplantation can serve as a diagnostic and prognostic tool to predict posttransplant complications, such as primary nonfunction, acute cellular rejection, or nonanastomotic biliary strictures. With the popularization of liver machine perfusion preservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 60 publications
(108 reference statements)
3
37
0
Order By: Relevance
“…In the CCA research process, the EVs in the culture media of CCA were separated mainly by ultracentrifugation [ 61 , 64 , 65 ]. Similarly, EVs are extracted from the serum by ultracentrifugation, and polymer-based precipitation kit [ 95 , 96 ]. However, there is a study that supports some commercial kits, such as ExoQuick and miR-CURY, as being better than ultracentrifugation, even with a limited quantity of EVs [ 92 ].…”
Section: Evs As Novel Biomarkers For Ccamentioning
confidence: 99%
See 1 more Smart Citation
“…In the CCA research process, the EVs in the culture media of CCA were separated mainly by ultracentrifugation [ 61 , 64 , 65 ]. Similarly, EVs are extracted from the serum by ultracentrifugation, and polymer-based precipitation kit [ 95 , 96 ]. However, there is a study that supports some commercial kits, such as ExoQuick and miR-CURY, as being better than ultracentrifugation, even with a limited quantity of EVs [ 92 ].…”
Section: Evs As Novel Biomarkers For Ccamentioning
confidence: 99%
“…However, there is a study that supports some commercial kits, such as ExoQuick and miR-CURY, as being better than ultracentrifugation, even with a limited quantity of EVs [ 92 ]. Bile is a lipid-rich fluid, that is secreted primarily by hepatocytes, and contains almost all body components: lipids, proteins, carbohydrates, vitamins, mineral salts and trace elements [ 96 , 97 ]. Because of the characteristics and complexity of bile extraction, we mainly summarize the isolation of bile here.…”
Section: Evs As Novel Biomarkers For Ccamentioning
confidence: 99%
“…Alternatively, perfusion at an intermediate temperature range (22)(23)(24)(25)(26)(27)(28)(29)(30) • C), termed subnormothermic machine perfusion (SNMP), has some potential advantages that warrant further exploration (3). At intermediate temperatures, the oxygen requirement of the graft is low enough to be met with a simple acellular perfusate, yet the metabolic activity of the graft is sufficiently high to support the production of bile, which is emerging as an important indicator of graft injury and viability (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that livers meeting hepatocellular viability criteria still developed biliary complications after transplantation 9,12 . Therefore, bile composition may be considered an additional parameter of bile duct viability 14 . This is underlined by a study showing low hepatocellular injury during NMP of discarded human livers but high bile duct injury on histology 15 .…”
mentioning
confidence: 99%